Economic globalization and the economic policy positions of parties - Sen, Sedef; Barry, Colin M (SAGE Publications, 2018)
Does economic globalization influence the economic policy positions adopted by political parties in democratic countries? In this article, we identify multiple pathways through which market integration might induce ideological change among both left and right parties. Utilizing data from 51 countries between 1970 and 2014, we evaluate the degree to which leftist and rightist economic ideologies, respectively, are present in parties’ platforms. We find that traditionally leftist positions are increasingly adopted by parties on both the right and the left in response to globalization. The evidence also suggests that, though there is a general tendency among parties to shift their economic platforms leftward in response to liberalization, there is significant between-country variability in the effects. An important implication of this study is that partisan ideological evolution is not driven solely by domestic forces, but by external factors, too.
Keywords: 4. Education; 8. Economic growth; 16. Peace & justice